2020
DOI: 10.1186/s12955-020-01321-3
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the situation of older family caregivers with a focus on health-related quality of life and pain: a cross-sectional cohort study

Abstract: Background: For a significant proportion of the older population, increasing age is associated with health problems and worsening health. Older family caregivers are largely responsible for care of next-of-kin living at home, which impacts their own physical and mental health both positively and negatively. However, evidence is insufficient regarding the health situation of older caregivers. The aim of this study was to investigate health-related quality of life (HRQoL) and pain, and their associations, among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
0
24
0
6
Order By: Relevance
“…Research, Society and Development, v. 10, n. 8, e13210817125, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i8.17125 evidenced (Altieri & Santangelo, 2021). Anxiety symptoms could be related to the mandatory isolation due to COVID-19, as people start to feel lonely, bored, or lacking activities (Hwang et al, 2020;Sallim et al, 2015), also, it can be aggravated due to caregiving responsibilities (Fagerström et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Research, Society and Development, v. 10, n. 8, e13210817125, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i8.17125 evidenced (Altieri & Santangelo, 2021). Anxiety symptoms could be related to the mandatory isolation due to COVID-19, as people start to feel lonely, bored, or lacking activities (Hwang et al, 2020;Sallim et al, 2015), also, it can be aggravated due to caregiving responsibilities (Fagerström et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…this finding is in agreement with that ofMoholt et al 13 who studied the factors affecting the use of home-based services and out of-home respite care services: A survey of family caregivers for older persons withdementia in Northern Norway whoreportedthat the more than three fifth of elderly caregivers were females . As well,Fagerström et al 14 who found in their study about the analyzing the situation of older family caregivers with a focus on health-related quality of life and pain: cross-sectional cohorts study in Sweden that, the great majority of their studied sample married This trend was opposite to what was found in a study in China byShi et al 12 whofound that, more than half of the studied sample were married men, in this regards James et al 3 revealed in their study about socio-demographic, health and functional status correlates of caregiver burden among care recipients age 60 Years and older in Jamaica that, more than half of the studied sample were single female. In Egypt, caregiving is a female occupation, and this give a reason why the majority of the study sample were more females than males.…”
Section: Resultsmentioning
confidence: 86%
“…The care of dependent people is associated with negative physical and mental health consequences for family caregivers [9][10][11]. The emotional and psychological consequences of caregiving are primarily represented by subjective burden [12], anxiety, depressive symptoms [13][14][15], higher levels of stress [16], lower levels of subjective well-being and self-efficacy [17], and low self-perceived quality of life [18,19]. Prevalence studies have shown that 40.2% of elderly relative caregivers present depressive symptoms [14].…”
Section: Introductionmentioning
confidence: 99%